A review of gelatin: Properties, sources, process, applications, and commercialisation. (2021) - Alipal, J.; Mohd Pu'ad, N.A.S.; Lee, T.C.; Nayan, N.H.M; Sahari, N.; Basri, H.; Idris, M.I.; Abdullah, H.Z.
Abstract: This review begins with a discussion of the general properties of gelatin and its sources, particularly in the food and health industries, and then briefly address the status quo of gelatin in today's market. Apart from the basic chemical compounds and gelatin types, this paper also discussed the commercialisation of gelatin. This study also highlights the production of conventional gelatin and its current method of processing, i.e. enzymatic hydrolysis. In addition, the variety of raw materials of collagen is outlined and briefly broached the plant hydrocolloids which have been labeled as 'veggie-gelatin'. With regard to the potential and market stability of gelatin, its recent studies are summarised in this paper. Accordingly, this paper focuses on assessing the general utilities of the various sources of collagen as gelatin derivatives. At that basis, the aim of this review is to provide an insight into gelatin in current applications, market value and progress in gelatin extraction.